Nanoporous Kevlar Aerogel Confined Phase Change Fluids Enable Super‐Flexible Thermal Diodes. (2nd February 2022) - Lyu, Jing; Sheng, Zhizhi; Xu, Yingying; Liu, Chenming; Zhang, Xuetong
Abstract: Aerogels have demonstrated tremendous potentials for various applications, including thermal insulation, environmental protection, and separation. However, aerogels as porous frameworks to host functional liquids (such as phase change fluids, PCFs) is a more promising application, attributing to their large specific surface area, high porosity, and strong capillary force. Herein, the original aramid nanofiber (OANF, i.e., Kevlar) aerogel film and the densified ANF (DANF) aerogel film are fabricated and thereafter applied to confine phase change fluids, poly (N‐isopropylacrylamide) (PNIPAM) solution and molten eicosane (C20), respectively, to make super‐flexible OANF‐PNIPAM and DANF‐C20 films accordingly. These two films exhibit reversely temperature‐dependent thermal conductivity with close phase change temperature to each other. Therefore, flexible thermal diodes operating with terminals of OANF‐PNIPAM film and DANF‐C20 film are proposed and fabricated, showing excellent flexibility (420 µm in curvature radius) and robustness (≥7.2 MPa in tensile strength) as well as the maximum thermal rectification ratio of 2.0. This work paves a way for expanding the applications of Kevlar aerogel confined phase change fluids, as well as provides a promising strategy for designing more practical thermal diodes and thermal devices. Abstract : The original aramid nanofiber aerogle film confined poly (N‐isopropylacrylamide) (OANF‐PNIPAM) and densified aramid nanofiber aerogel film confined eicosane (DANF‐C20) are fabricated, respectively, which exhibit reversely temperature‐dependent thermal conductivity, approximate phase change temperatures, and incompatible interfaces with opposite hydrophobicity. Based on these two films, a flexible thermal diode is proposed and fabricated, showing excellent flexibility and robustness as well as satisfactory thermal rectification.